Analisis Dampak Kebijakan Otoritas Jasa Keuangan (OJK) Terhadap Pertumbuhan Perbankan Syariah di Indonesia - Dinda Putri Ramadhani; Lolla Amelia; Robi Saputra; Keyzia Salma Nabilla; Hendri Hendri (LPPM Universitas Sains dan Teknologi Komputer, 2026)
The purpose of this study is to examine how the Financial Services Authority's (OJK) regulation has affected Indonesia's sharia banking industry's rapid expansion in the face of digital and international economic problems. As a supervisory and regulatory authority, OJK has a vital role in determining the direction of policy through structural and operational regulatory instruments. The impact of the Indonesian Sharia Banking Development and Strengthening Roadmap (RP3SI) and rules pertaining to the requirement to separate (spin-off) Sharia Business Units (UUS) in accordance with POJK Number 12 of 2023 are the primary subjects of this study. Using a policy analysis technique and an examination of secondary data from the Sharia Financial Development Report, a qualitative descriptive research methodology was employed. The analysis's findings demonstrate that through consolidation incentives, the OJK regulation has greatly improved the capital and governance of sharia banking. Regulatory intervention in the digitalization aspect is also proven to increase operational efficiency and expand the range of services to the community. However, this study also found a challenge in policy synchronization, where asset growth has not been followed linearly by an increase in market share (market share) which is still held below 10%. The main barriers identified include limited product differentiation as well as low sharia financial literacy among the community. The conclusion of this study emphasizes that although the OJK policy has provided a strong legal foundation for industrial stability, more progressive incentives and cross-sectoral collaboration in the halal economic ecosystem are needed to spur more exponential growth. This study provides important implications for regulators to evaluate policy communication strategies to be more adaptive to market dynamics.